Comparison of apical sealing ability of bioceramic sealer and epoxy resin-based sealer using the fluid filtration technique and scanning electron microscopy - Widcha Asawaworarit; Thitapa Pinyosopon; Kanittha Kijsamanmith (Elsevier, 2020)
Background/purpose: A perfect sealing of root canal system is essential for preventing ingress of bacteria from the oral environment. The purpose of this study was to evaluate the apical sealing ability of bioceramic (EndoSequence BC Sealer®) and epoxy resin-based (AH Plus®) sealers at 24 h, 7 days and 4 weeks. Materials and methods: Forty two extracted human upper anterior teeth were sectioned to leave the root 15-mm long, then all the roots were instrumented using a set of ProTaper® rotary instruments. Four roots were selected randomly as controls, and the remaining 38 roots were randomly divided into 2 groups of 19 roots each: group 1: EndoSequence BC Sealer® and gutta-percha, and group 2: AH Plus® and gutta-percha using a multiple wave condensation technique. The apical sealing ability of the filled root canal was measured using the fluid filtration method with 200 mmHg (26.67 KPa) above atmospheric pressure at 24 h, 7 days and 4 weeks. Scanning electron microscopy (SEM) was used to assess the adaptation and penetration of the sealers. The apical microleakage between 2 groups was compared using Student's t-test. P < 0.05 was considered statistically significant. Results: EndoSequence BC Sealer® had significantly better sealing ability than AH Plus® at all test periods (P < 0.001). SEM showed EndoSequence BC Sealer® had better penetration into dentinal tubules. Conclusion: Bioceramic sealer could promote proper sealing of root canals obturated with multiple wave condensation.